2012
DOI: 10.5535/arm.2012.36.4.433
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of ACE Activity according to ACE I/D Polymorphisms on Muscular Functions of People Aged 65

Abstract: ObjectiveTo investigate associations between angiotensin-converting enzyme (ACE) polymorphisms and muscle fatigability in 65-year-old Koreans.MethodThe study participants were 49 Koreans aged 65 years. ACE insertion/deletion (I/D) polymorphisms were determined by polymerase chain reaction and serum ACE activity, by spectrophotometry. Body mass index (BMI), body fat mass (BFM), and lean body mass (LBM) were determined. To evaluate muscle fatigability, dynamic Electromyography was used to measure maximum volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…ACE activity and ACE polymorphism were generally not connected with muscle strength. 34 37 Kang et al 34 showed no interrelation between the handgrip strength and the ACE activity (but showed it for muscle fatigability) among older Koreans. Similarly, Bustamante-Ara et al 35 reported no association between ACE genotype and handgrip strength as well as leg press strength and functional performance measured with walking speed and step test in nonagenarians.…”
Section: Discussionmentioning
confidence: 99%
“…ACE activity and ACE polymorphism were generally not connected with muscle strength. 34 37 Kang et al 34 showed no interrelation between the handgrip strength and the ACE activity (but showed it for muscle fatigability) among older Koreans. Similarly, Bustamante-Ara et al 35 reported no association between ACE genotype and handgrip strength as well as leg press strength and functional performance measured with walking speed and step test in nonagenarians.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, among older people deletion polymorphism of ACE gene (DD), connected with higher level of angiotensin II, was associated with low muscle mass 33 . Similarly, advanced cancer patients with DD ACE gene polymorphism were characterized by higher serum ACE activity but lower hand grip strength compared with ACE insertion group 34,35 .…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies suggest that individuals with a higher frequency of the ACE DD genotype have greater strength/power than those with genotype II and ID overexpression [ 32 ]. A recent meta-analysis study found that the predominance of ACE genotype II is indicated as advantageous for the performance of individuals aiming for endurance performance [ 33 ].…”
Section: Discussionmentioning
confidence: 99%